The Dirichlet-tree Distribution - Minka, Tom (1999)
This note further explores the Dirichlet-tree distribution developed by Dennis (1991). An inclusion relationship is given for different tree structures and an independence relationship is given for probabilities in the tree. The posterior, evidence, and predictive density are derived for multinomial observations.